2017
DOI: 10.1016/j.exer.2016.03.005
|View full text |Cite
|
Sign up to set email alerts
|

The lens actin filament cytoskeleton: Diverse structures for complex functions

Abstract: The eye lens is a transparent and avascular organ in the front of the eye that is responsible for focusing light onto the retina in order to transmit a clear image. A monolayer of epithelial cells covers the anterior hemisphere of the lens, and the bulk of the lens is made up of elongated and differentiated fiber cells. Lens fiber cells are very long and thin cells that are supported by sophisticated cytoskeletal networks, including actin filaments at cell junctions and the spectrin-actin network of the membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 229 publications
(278 reference statements)
0
44
0
Order By: Relevance
“…We observed that tdTomato labeling is bright and stable and can be easily observed in lens cells as deep as 150m from the capsule surface ( Figure 1B). Additionally, the characteristic cobble stone morphology of the anterior epithelial cell monolayer and the fiber cell tips at the Y-shaped sutures of mouse lenses (Kuszak et al, 1984;Cheng et al, 2017b) are apparent with endogenous tdTomato labeling ( Figure 1C).…”
Section: Tdtomato Labeling Of Mouse Lenses Allows Live Visualization mentioning
confidence: 90%
See 1 more Smart Citation
“…We observed that tdTomato labeling is bright and stable and can be easily observed in lens cells as deep as 150m from the capsule surface ( Figure 1B). Additionally, the characteristic cobble stone morphology of the anterior epithelial cell monolayer and the fiber cell tips at the Y-shaped sutures of mouse lenses (Kuszak et al, 1984;Cheng et al, 2017b) are apparent with endogenous tdTomato labeling ( Figure 1C).…”
Section: Tdtomato Labeling Of Mouse Lenses Allows Live Visualization mentioning
confidence: 90%
“…The capsule, which is rich in type IV collagen, surrounds the entire organ (Lovicu and Robinson, 2004). Inward from the capsule are the lens cells, which have intricate shapes and are highly organized (Wanko and Gavin, 1959;Cheng et al, 2017b). A monolayer of epithelial cells covers the anterior hemisphere of the lens and is attached to the capsule.…”
Section: Introductionmentioning
confidence: 99%
“…Lens membrane are rich in cholesterol and sphingolipids, resulting in the formation of lipid rafts [259, 260]. Lens cytoskeleton is comprised of spectrin-actin system anchored by membrane protein Band 3 similar to other cell types [315]. The intermediate filament proteins Bfsp1 (filensin) and Bfsp2 (phakinin) are highly lens-specific while vimentin is a ubiqitously expressed protein [316–318].…”
Section: Figurementioning
confidence: 99%
“…In mammals, the lens develops from a placode of head ectoderm under the influence of a paired box 6 (PAX6)-dependent gene regulatory network and several extracellular signaling pathways to form an exquisitely patterned, cellular structure composed of two cell types enclosed in a collagenous basement membrane or capsule. (Bassnett et al, 2011; Cheng et al, 2017b; Cvekl and Zhang, 2017). The anterior lens surface comprises a monolayer of mitotically competent epithelial cells that terminally differentiate at the lens equator into concentric layers (growthshells) of tightly packed, highly elongated, secondary fiber cells that form the refractive mass of the lens.…”
Section: Introductionmentioning
confidence: 99%
“…The anterior lens surface comprises a monolayer of mitotically competent epithelial cells that terminally differentiate at the lens equator into concentric layers (growthshells) of tightly packed, highly elongated, secondary fiber cells that form the refractive mass of the lens. Lens fiber cell formation is characterized by several unique re-modeling processes including accumulation of crystallins in the cytoplasm, remodeling of the cytoskeleton, specialization of the plasma-membrane, programmed loss of organelles, and formation of a core syncytium (Bassnett et al, 2011; Cheng et al, 2017b; Cvekl and Zhang, 2017). Collectively, these cellular processes are designed to establish and maintain lens transparency, minimize light scattering, and generate a high refractive index.…”
Section: Introductionmentioning
confidence: 99%